Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Counter-propagating photon pair generation in a nonlinear waveguide - Luo, Kai-Hong; Ansari, Vahid; Massaro, Marcello; Santandrea, Matteo; Eigner, Christof; Ricken, Raimund; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Nonlinear optics in all-dielectric nanoantennas and metasurfaces: a review - Sain, Basudeb; Meier, Cedrik; Zentgraf, Thomas (Advanced Photonics)
Free from phase-matching constraints, plasmonic metasurfaces have contributed significantly to the control of optical nonlinearity and enhancement of nonlinear generation efficiency by engineering subwavelength meta-atoms. However, high dissipative losses and inevitable thermal heating limit their applicability in nonlinear nanophotonics. All-dielectric metasurfaces, supporting both electric and magnetic Mie-type resonances in their nanostructures, have appeared as a promising alternative to nonlinear plasmonics. High-index dielectric nanostructures, allowing additional magnetic resonances, can induce magnetic nonlinear effects, which, along with electric nonlinearities, increase the nonlinear conversion efficiency. In addition, low dissipative losses and high damage thresholds provide an extra degree of freedom for operating at high pump intensities, resulting in a considerable enhancement of the nonlinear processes. We discuss the current state of the art in the intensely developing area of all-dielectric nonlinear nanostructures and metasurfaces, including the role of Mie modes, Fano resonances, and anapole moments for harmonic generation, wave mixing, and ultrafast optical switching. Furthermore, we review the recent progress in the nonlinear phase and wavefront control using all-dielectric metasurfaces. We discuss techniques to realize all-dielectric metasurfaces for multifunctional applications and generation of second-order nonlinear processes from complementary metal–oxide–semiconductor-compatible materials.

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Zinc oxide based dielectric nanoantennas for efficient nonlinear frequency conversion - Golla, C.; Weber, N.; Meier, Cedrik (Journal of Applied Physics)

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Nonreciprocal Asymmetric Polarization Encryption by Layered Plasmonic Metasurfaces - Frese, Daniel; Wei, Qunshuo; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
As flexible optical devices that can manipulate the phase and amplitude of light, metasurfaces would clearly benefit from directional optical properties. However, single layer metasurface systems consisting of two-dimensional nanoparticle arrays exhibit only a weak spatial asymmetry perpendicular to the surface and therefore have mostly symmetric transmission features. Here, we present a metasurface design principle for nonreciprocal polarization encryption of holographic images. Our approach is based on a two-layer plasmonic metasurface design that introduces a local asymmetry and generates a bidirectional functionality with full phase and amplitude control of the transmitted light. The encoded hologram is designed to appear in a particular linear cross-polarization channel, while it is disappearing in the reverse propagation direction. Hence, layered metasurface systems can feature asymmetric transmission with full phase and amplitude control and therefore expand the design freedom in nanoscale optical devices toward asymmetric information processing and security features for anticounterfeiting applications.

Reconfigurable metasurface hologram by utilizing addressable dynamic pixels - Li, Tianyou; Wei, Qunshuo; Reineke, Bernhard; Walter, Felicitas; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Optics Express)

Silicon metasurfaces for third harmonic geometric phase manipulation and multiplexed holography - Reineke, Bernhard; Sain, Basudeb; Zhao, Ruizhe; Carletti, Luca; Liu, Bingyi; Huang, Lingling; de Angelis, Costantino; Zentgraf, Thomas (Nano Letters)

Metasurface interferometry toward quantum sensors - Georgi, Philip; Massaro, Marcello; Luo, Kai Hong; Sain, Basudeb; Montaut, Nicola; Herrmann, Harald; Weiss, Thomas; Li, Guixin; Silberhorn, Christine; Zentgraf, Thomas (Light: Science & Applications)

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Simultaneous Spectral and Spatial Modulation for Color Printing and Holography Using All-dielectric Metasurfaces - Wei, Qunshuo; Sain, Basudeb; Wang, Yongtian; Reineke, Bernhard; Li, Xiaowei; Huang, Lingling; Zentgraf, Thomas (Nano Letters)

Four‐Wave Mixing Holographic Multiplexing Based on Nonlinear Metasurfaces - Lin, Zemeng; Huang, Lingling; Xu, Zhen Tao; Li, Xiaowei; Zentgraf, Thomas; Wang, Yongtian (Advanced Optical Materials)

Dynamic control of mode modulation and spatial multiplexing using hybrid metasurfaces - Lin, Zemeng; Huang, Lingling; Zhao, Ruizhe; Wei, Qunshuo; Zentgraf, Thomas; Wang, Yongtian; Li, Xiaowei (Optics Express)

Miniaturized Metalens Based Optical Tweezers on Liquid Crystal Droplets for Lab-on-a-Chip Optical Motors - Suwannasopon, Satayu; Meyer, Fabian; Schlickriede, Christian; Chaisakul, Papichaya; T-Thienprasert, Jiraroj; Limtrakul, Jumras; Zentgraf, Thomas; Chattham, Nattaporn (Crystals)
Surfaces covered with layers of ultrathin nanoantenna structures—so called metasurfaces have recently been proven capable of completely controlling phase of light. Metalenses have emerged from the advance in the development of metasurfaces providing a new basis for recasting traditional lenses into thin, planar optical components capable of focusing light. The lens made of arrays of plasmonic gold nanorods were fabricated on a glass substrate by using electron beam lithography. A 1064 nm laser was used to create a high intensity circularly polarized light focal spot through metalens of focal length 800 µm, N.A. = 0.6 fabricated based on Pancharatnam-Berry phase principle. We demonstrated that optical rotation of birefringent nematic liquid crystal droplets trapped in the laser beam was possible through this metalens. The rotation of birefringent droplets convinced that the optical trap possesses strong enough angular momentum of light from radiation of each nanostructure acting like a local half waveplate and introducing an orientation-dependent phase to light. Here, we show the success in creating a miniaturized and robust metalens based optical tweezers system capable of rotating liquid crystals droplets to imitate an optical motor for future lab-on-a-chip applications.

Strong Nonlinear Optical Activity Induced by Lattice Surface Modes on Plasmonic Metasurface - Chen, Shumei; Reineke, Bernhard; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Nano Letters)

Herstellung von Wellenleitern aus Materialien der KTP-Familie - Padberg, Laura; Eigner, Christof; Santandrea, Matteo; Silberhorn, Christine

Efficient C-band single-photon upconversion with chip-scale Ti-indiffused pp-LiNbO3 waveguides - Xie, Zhenda; Luo, Kai Hong; Chang, Kai Chi; Panoiu, Nicolae C.; Herrmann, Harald; Silberhorn, Christine; Wong, Chee Wei (Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Estimating the Indistinguishability of Heralded Single Photons Using Second-Order Correlation - Faruque, Imad I.; Sinclair, Gary F.; Bonneau, Damien; Ono, Takafumi; Silberhorn, Christine; Thompson, Mark G.; Rarity, John G. (Physical Review Applied)
Keywords: General Physics and Astronomy

Temporally multimode four-photon Hong-Ou-Mandel interference - Ferreri, Alessandro; Ansari, V.; Silberhorn, Christine; Sharapova, Polina R. (Physical Review A)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Mode-independent quantum entanglement for light - Sperling, Jan; Perez-Leija, Armando; Busch, Kurt; Silberhorn, Christine (Physical Review A)

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)
DNA origami nanostructures are versatile substrates for the controlled arrangement of molecular capture sites with nanometer precision and thus have many promising applications in singlemolecule bioanalysis. Here, we investigate the adsorption of DNA origami nanostructures in nanohole arrays which represent an important class of biosensors and may benefit from the incorporation of DNA origami-based molecular probes. Nanoholes with well-defined diameter that enable the adsorption of single DNA origami triangles are fabricated in Au films on Siwafers by nanosphere lithography. The efficiency of directed DNA origami adsorption on the exposed SiO2 areas at the bottoms of the nanoholes is evaluated in dependence of various parameters, i.e., Mg2+ and DNA origami concentrations, buffer strength, adsorption time, and nanohole diameter. We observe that the buffer strength has a surprisingly strong effect on DNA origami adsorption in the nanoholes and that multiple DNA origami triangles with 120 nm edge length can adsorb in nanoholes as small as 120 nm in diameter. We attribute the latter observation to the low lateral mobility of once adsorbed DNA origami on the SiO2 surface, in combination with parasitic adsorption to the Au film. While parasitic adsorption can be suppressed by modifying the Au film with a hydrophobic self-assembled monolayer, the limited surface mobility of the adsorbed DNA origami still leads to poor localization accuracy in the nanoholes and results in many DNA origami crossing the boundary to the Au film even under optimized conditions. We discuss possible ways to minimize this effect by varying the composition of the adsorption buffer, employing different fabrication conditions, or using other substrate materials for nanohole array fabrication.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Photonic crystal properties of Si and SiO2 nanopillar arrays fabricated by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Wu, Xia; Wagner, Thorsten; Lindner, Jörg

Strain Relaxation in InAs Nanoislands on top of GaAs (111) A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

MBE Growth of InAs on Nanopillar-Patterned GaAs (111) A - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Reuter, Dirk; Lindner, Jörg

Impact of shell growth on recombination dynamics and exciton-phonon interaction in CdSe-CdS core-shell nanoplatelets - Achtstein, Alexander W.; Marquardt, Oliver; Scott, Riccardo; Ibrahim, Mohamed; Riedl, Thomas; Prudnikau, Anatol V.; Antanovich, Artsiom; Owschimikow, Nina; Lindner, Jörg; Artemyev, Mikhail; Woggon, Ulrike (accepted 05.09.2018)

Self-assembled Surface Patterns for Controlled Nanoparticle Placement and Improved Semiconductor Heteroepitaxy - Brassat, Katharina; Riedl, Thomas; Lindner, Jörg

Exciton-Phonon Interaction in Core-Only, Core-Shell Nanoplatelets and Quantum Dots - Scott, Riccardo; Prudnikau, Anatol; Antanovich, Artsiom; Christodoulou, Soririos; Riedl, Thomas; Bertrand, Guilaume; Owschimikow, Nina; Lindner, Jörg; Hens, Zeger; Moreels, Iwan; Artemyev, Mikhail; Woggon, Ulrike; et al. (submitted to Nano Letters)

Stability of Heteroepitaxial Coherent Growth Modes on Nanowire Radial Surfaces - Riedl, Thomas; Lindner, Jörg (submitted to Phys. Rev. Mat.)

Modification of block copolymer lithography masks by O2 plasma treatment: Insights from lift off experiments, nanopore etching and free membranes - Brassat, Katharina; Kool, Daniel; Lindner, Jörg (To be submitted)

Nanostructure Research using Transmission Electron Microscopy at the new OWL Analytic Centre - Riedl, Thomas; Bürger, Julius; Kunnathully, Vinay; Wiegand, Marie; Duschik, K.; Ramermann, D.; Ennen, I.; Hertle, Y.; Schaper, Mirko; Hellweg, T.; Hütten, A.; Lindner, Jörg

State-of-the-art transmission electron microscopy in the imaging and scanning mode - Lindner, Jörg

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim J.; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

Hierarchical nanopores formed by block copolymer lithography on the surfaces of different materials pre-patterned by nanosphere lithography - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg (Nanoscale)
Bottom-up patterning techniques allow for the creation of surfaces with ordered arrays of nanoscale features on large areas. Two bottom-up techniques suitable for the formation of regular nanopatterns on different length scales are nanosphere lithography (NSL) and block copolymer (BCP) lithography. In this paper it is shown that NSL and BCP lithography can be combined to easily design hierarchically nanopatterned surfaces of different materials. Nanosphere lithography is used for the pre-patterning of surfaces with antidots, i.e. hexagonally arranged cylindrical holes in thin films of Au, Pt and TiO2 on SiO2, providing a periodic chemical and topographical contrast on the surface suitable for templating in subsequent BCP lithography. PS-b-PMMA BCP is used in the second self-assembly step to form hexagonally arranged nanopores with sub-20 nm diameter within the antidots upon microphase separation. To achieve this the microphase separation of BCP on planar surfaces is studied, too, and it is demonstrated for the first time that vertical BCP nanopores can be formed on TiO2, Au and Pt films without using any neutralization layers. To explain this the influence of surface energy, polarity and roughness on the microphase separation is investigated and discussed along with the wetting state of BCP on NSL-pre-patterned surfaces. The presented novel route for the creation of advanced hierarchical nanopatterns is easily applicable on large-area surfaces of different materials. This flexibility makes it suitable for a broad range of applications, from the morphological design of biocompatible surfaces for life science to complex pre-patterns for nanoparticle placement in semiconductor technology.

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)
Dodecyl amine edge functionalized few-layer graphene oxide quantum dots were synthesized in good yields. The covalent functionalization was demonstrated with NMR and AFM-IR. The resulting structure and particle size was measured with AFM and HRTEM. The thermal stability of the compound was investigated and showed a stability of up to 220 °C. The modified graphene oxide quantum dots showed excellent solubility in various organic solvents, including ethers, methanol, toluene, n-hexane, heptane, xylene, dichloromethane and toluene. The stability of a resulting toluene solution was also proven by static light scattering measurements over several days. The excellent solubility gives the possibility of an efficient and fast spray application of the functionalized graphene oxide quantum dots to steel surfaces. Hence, the macroscopic friction behavior was investigated with a Thwing-Albert FP-2250 friction tester. A thin film of the dodecyl amine functionalized graphene oxide quantum dots on steel lowered the friction coefficient from 0.17 to 0.11 and revealed a significant corrosion inhibition effect.

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Site-specific formation of nanoscaled protein structures is a challenging task. Most known structuring methods are either complex and hardly upscalable or do not apply to biological matter at all. The presented combination of enzyme mediated autodeposition and nanosphere lithography provides an easy-to-apply approach for the buildup of protein nanostructures over a large scale. The key factor is the tethering of enzyme to the support in designated areas. Those areas are provided via prepatterning of enzymatically active antidots with variable diameters. Enzymatically triggered protein addressing occurs exclusively at the intended areas and continues until the entire active area is coated. After this, the reaction self-terminates. The major advantage of the presented method lies in its easy applicability and upscalability. Large area structuring of entire support surfaces with features on the nanometer scale is performed efficiently and without the necessity of harsh conditions. These are valuable premises for large-scale applications with potentials in biosensor technology, nanoelectronics, and life sciences.

With directed self-arrangement of DNA origami to large-area quantum dot arrays - Grundmeier, Guido; Brassat, Katharina; Keller, A.; Lindner, Jörg

Hierarchical nanopore and nanoring arrays by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Lindner, Jörg

Ti-6Al-4V alloy: 3D printing of lightweight implants and nanopatterning by self-assembly - Brassat, Katharina; Taube, A.; Kool, Daniel; Tasche, L.; Hoyer, K.P.; Schaper, Mirko; Lindner, Jörg

Morphology investigation of nanopores by block copolymer lithography on different material surfaces - Brassat, Katharina; Kool, Daniel; Taube, A.; Schaper, Mirko; Lindner, Jörg

Nanoscopic protein arrays on BCP prepatterned surfaces - Brassat, Katharina; Brüngeler, A.; Bremser, W.; Strube, O.I.; Lindner, Jörg

Hierarchical nanopatterns by site-selective DNA origami adsoprtion on pre-patterned surfaces - Brassat, Katharina; Ramakrishna, S.; Keller, A.; Lindner, Jörg

Simulation of Transport Processes during the Convective Self-Assembly of Colloidal Nanomasks - Drude, Dennis; Lindner, Jörg

Protein and DNA origami arrays on large areas by directed self-assembly - Brassat, Katharina; Bremser, W.; Strube, O.; Grundmeier, G.; Keller, A.; Lindner, Jörg

Selbstorganisation für die Nanotechnik von morgen - Lindner, Jörg

Nanoscale materials and interface design by self-organization - Lindner, Jörg

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Efficient frequency conversion by combined photonic–plasmonic mode coupling - Weber, N.; Hoffmann, S. P.; Albert, M.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

High-performance source of spectrally pure, polarization entangled photon pairs based on hybrid integrated-bulk optics - Meyer-Scott, Evan; Prasannan, Nidhin; Eigner, Christof; Quiring, Viktor; Donohue, John M.; Barkhofen, Sonja; Silberhorn, Christine (Optics Express)

High-power waveguide resonator second harmonic device with external conversion efficiency up to 75% - Stefszky, Michael; Ricken, R; Eigner, Christof; Quiring, V; Herrmann, Harald; Silberhorn, Christine (Journal of Optics)

Compressive characterization of telecom photon pairs in the spatial and spectral degrees of freedom - Montaut, Nicola; Magaña-Loaiza, Omar S.; Bartley, Tim; Verma, Varun B.; Nam, Sae Woo; Mirin, Richard P.; Silberhorn, Christine; Gerrits, Thomas (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Streak camera imaging of single photons at telecom wavelength - Allgaier, Markus; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Donohue, John Matthew; Czerniuk, Thomas; Aßmann, Marc; Bayer, Manfred; Brecht, Benjamin; Silberhorn, Christine (Applied Physics Letters)

Quantum-Limited Time-Frequency Estimation through Mode-Selective Photon Measurement - Donohue, J. M.; Ansari, V.; Řeháček, J.; Hradil, Z.; Stoklasa, B.; Paúr, M.; Sánchez-Soto, L. L.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Electromagnetically Induced Transparency of On-demand Single Photons in a Hybrid Quantum Network - Schweickert, Lucas; Jöns, Klaus D.; Namazi, Mehdi; Cui, Guodong; Lettner, Thomas; Zeuner, Katharina D.; Montaña, Lara Scavuzzo; Silva, Saimon Filipe Covre da; Reindl, Marcus; Huang, Huiying; Trotta, Rinaldo; Rastelli, Armando; et al. (arXiv:1808.05921)
Long range quantum communication and quantum information processing require the development of light-matter interfaces for distributed quantum networks. Even though photons are ideal candidates for network links to transfer quantum information, the system of choice for the realization of quantum nodes has not been identified yet. Ideally, one strives for a hybrid network architecture, which will consist of different quantum systems, combining the strengths of each system. However, interfacing different quantum systems via photonic channels remains a major challenge because a detailed understanding of the underlying light-matter interaction is missing. Here, we show the coherent manipulation of single photons generated on-demand from a semiconductor quantum dot using a rubidium vapor quantum memory, forming a hybrid quantum network. We demonstrate the engineering of the photons' temporal wave function using four-level atoms and the creation of a new type of electromagnetic induced transparency for quantum dot photons on resonance with rubidium transitions. Given the short lifetime of our quantum dot transition the observed dynamics cannot be explained in the established steady-state picture. Our results play a pivotal role in understanding quantum light-matter interactions at short time scales. These findings demonstrate a fundamental active node to construct future large-scale hybrid quantum networks.

Manipulation of Two-Photon Interference by Entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Conference on Lasers and Electro-Optics)

Incomplete Detection of Nonclassical Phase-Space Distributions - Bohmann, M.; Tiedau, J.; Bartley, Tim; Sperling, Jan; Silberhorn, Christine; Vogel, W. (Physical Review Letters)

Monolithically Integrated Hong-Ou-Mandel Experiment in LiNbO3 - Luo, Kai Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Conference on Lasers and Electro-Optics)

Imaging of 180∘ ferroelectric domain walls in uniaxial ferroelectrics by confocal Raman spectroscopy: Unraveling the contrast mechanism - Rüsing, Michael; Neufeld, Sergej; Brockmeier, Julian; Eigner, Christof; Mackwitz, P.; Spychala, K.; Silberhorn, Christine; Schmidt, Wolf Gero; Berth, Gerhard; Zrenner, Artur; Sanna, S. (Physical Review Materials)
In recent years, Raman spectroscopy has been used to visualize and analyze ferroelectric domain structures. The technique makes use of the fact that the intensity or frequency of certain phonons is strongly influenced by the presence of domain walls. Although the method is used frequently, the underlying mechanism responsible for the changes in the spectra is not fully understood. This inhibits deeper analysis of domain structures based on this method. Two different models have been proposed. However, neither model completely explains all observations. In this work, we have systematically investigated domain walls in different scattering geometries with Raman spectroscopy in the common ferroelectric materials used in integrated optics, i.e., KTiOPO4, LiNbO3, and LiTaO3. Based on the two models, we can demonstrate that the observed contrast for domain walls is in fact based on two different effects. We can identify on the one hand microscopic changes at the domain wall, e.g., strain and electric fields, and on the other hand a macroscopic change of selection rules at the domain wall. While the macroscopic relaxation of selection rules can be explained by the directional dispersion of the phonons in agreement with previous propositions, the microscopic changes can be explained qualitatively in terms of a simplified atomistic model.

Volumetric Generation of Optical Vortices with Metasurfaces - Huang, Lingling; Song, Xu; Reineke, Bernhard; Li, Tianyou; Li, Xiaowei; Liu, Juan; Zhang, Shuang; Wang, Yongtian; Zentgraf, Thomas (ACS Photonics)

Zn–VI quasiparticle gaps and optical spectra from many-body calculations - Riefer, Arthur; Weber, Nils; Mund, Johannes; Yakovlev, Dmitri R.; Bayer, Manfred; Schindlmayr, Arno; Meier, Cedrik; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)
The electronic band structures of hexagonal ZnO and cubic ZnS, ZnSe, and ZnTe compounds are determined within hybrid-density-functional theory and quasiparticle calculations. It is found that the band-edge energies calculated on the G0W0 (Zn chalcogenides) or GW (ZnO) level of theory agree well with experiment, while fully self-consistent QSGW calculations are required for the correct description of the Zn 3d bands. The quasiparticle band structures are used to calculate the linear response and second-harmonic-generation (SHG) spectra of the Zn–VI compounds. Excitonic effects in the optical absorption are accounted for within the Bethe–Salpeter approach. The calculated spectra are discussed in the context of previous experimental data and present SHG measurements for ZnO.

Fabrication of low-loss Rb-exchanged ridge waveguides in z-cut KTiOPO_4 - Volk, Martin F.; Rüter, Christian E.; Santandrea, Matteo; Eigner, Christof; Padberg, Laura; Herrmann, Harald; Silberhorn, Christine; Kip, Detlef (Optical Materials Express)

A monolithic, doubly-resonant parametric down-conversion source for Caesium Raman memories - Brecht, Benjamin; Lazo-Arjona, O.; Kaczmarek, K. T.; Parker, T.; Ricken, R.; Quiring, V.; Eigner, Christof; Luo, K. H.; Herrmann, Harald; Silberhorn, Christine; Walmsley, I. A. (Frontiers in Optics 2017)

Waveguide Cavity Resonator as a Source of Optical Squeezing - Stefszky, M.; Ricken, R.; Eigner, Christof; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)

A two-channel, spectrally degenerate polarization entangled source on chip - Sansoni, Linda; Luo, Kai Hong; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (npj Quantum Information)

Heteroepitaxy of III–V Zinc Blende Semiconductors on Nanopatterned Substrates - Riedl, Thomas; Lindner, Jörg (Nanoscaled Films and Layers)
In the last decade, zinc blende structure III–V semiconductors have been increasingly utilized for the realization of high‐performance optoelectronic applications because of their tunable bandgaps, high carrier mobility and the absence of piezoelectric fields. However, the integration of III–V devices on the Si platform commonly used for CMOS electronic circuits still poses a challenge, due to the large densities of mismatch‐related defects in heteroepitaxial III–V layers grown on planar Si substrates. A promising method to obtain thin III–V layers of high crystalline quality is the growth on nanopatterned substrates. In this approach, defects can be effectively eliminated by elastic lattice relaxation in three dimensions or confined close to the substrate interface by using aspect‐ratio trapping masks. As a result, an etch pit density as low as 3.3 × 10^5 cm^−2 and a flat surface of submicron GaAs layers have been accomplished by growth onto a SiO2 nanohole film patterned Si(001) substrate, where the threading defects are trapped at the SiO2 mask sidewalls. An open issue that remains to be resolved is to gain a better understanding of the interplay between mask shape, growth conditions and formation of coalescence defects during mask overgrowth in order to achieve thin device quality III–V layers

Joining self-assembly techniques: A route to hierarchical nanopores - Brassat, Katharina; Lindner, Jörg

Micro- and nanopatterned surfaces with tailored chemical and topographical contrast by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg

Tailored antidot patterns created by nanosphere lithography for bioapplications - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Morphological properties of nanopillar patterned Si surfaces obtained by nanosphere lithography and metal-assisted wet-chemical etching - Kismann, Michael; Riedl, Thomas; Lindner, Jörg

InAs heteroepitaxy on GaAs patterned by nanosphere lithography - Kunnathully, Vinay; Riedl, Thomas; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Group III arsenide heteroepitaxy on Si(111) using SiNx nanohole masks patterned by nanosphere lithography - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Lindner, Jörg

Morphology, structure and enhanced PL of molecular beam epitaxial In0.2Ga0.8As layers on nanopillar patterned GaAs - Riedl, Thomas; Kunnathully, Vinay; Karlisch, A.; Reuter, Dirk; Weber, N.; Meier, Cedrik; Schierholz, R.; Lindner, Jörg

Strain and strain energy in axial-heteroepitaxial GaAs/InAs nanopillars analyzed by atomistic and continuum elastic calculations - Riedl, Thomas; Lindner, Jörg

The influence of the sphere material on the opening size distribution of nanosphere lithography masks - Riedl, Thomas; Lindner, Jörg

Evolution of the opening size of nanosphere lithography masks during thermal annealing - Riedl, Thomas; Kunnathully, Vinay; Lindner, Jörg

Strain Compensation in Single ZnSe/CdSe Quantum Wells: Analytical Model and Experimental Evidence - Rieger, Torsten; Riedl, Thomas; Neumann, Elmar; Grützmacher, Detlev; Lindner, Jörg; Pawlis, Alexander (ACS Applied Materials & Interfaces)

Strain effects on the heteroepitaxy of III-V compound semiconductors on nanopatterned surfaces - Lindner, Jörg; Riedl, Thomas

Ion Beam Modification of Self-Organized Nanostructures - Lindner, Jörg

Bioinspired material design by hierarchical self-assembly on prepatterned surfaces - Brassat, Katharina; Keller, A.; Grundmeier, G.; Bremser, W.; Strube, O.; Lindner, Jörg

Regular surface nanopatterning with nanosphere lithography, block copolymer lithography and cominations of both - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Directional Emission from Dielectric Leaky-Wave Nanoantennas - Peter, Manuel; Hildebrandt, Andre; Schlickriede, Christian; Gharib, Kimia; Zentgraf, Thomas; Förstner, Jens; Linden, Stefan (Nano Letters)
Keywords: tet_topic_opticalantenna

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Ultrathin Nonlinear Metasurface for Optical Image Encoding - Walter, Felicitas; Li, Guixin; Meier, Cedrik; Zhang, Shuang; Zentgraf, Thomas (Nano Letters)

Identifying and Realizing Symmetries in Quantum Walks - Symmetry Classes and Quantum Walks - Schütte, Philipp

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Plasmonic nanostructures: spectroscopy and electron microscopy - Kitzerow, Heinz-Siegfried; Lindner, Jörg

Limits of the time-multiplexed photon-counting method - Kruse, Regina; Tiedau, Johannes; Bartley, Tim; Barkhofen, Sonja; Silberhorn, Christine (Physical Review A)

Driven Boson Sampling - Barkhofen, Sonja; Bartley, Tim; Sansoni, Linda; Kruse, Regina; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review Letters)

High-Efficiency Plug-and-Play Source of Heralded Single Photons - Montaut, Nicola; Sansoni, Linda; Meyer-Scott, Evan; Ricken, Raimund; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Physical Review Applied)
Keywords: General Physics and Astronomy

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Harnessing temporal modes for multi-photon quantum information processing based on integrated optics - Harder, G.; Ansari, V.; Bartley, Tim; Brecht, Benjamin; Silberhorn, Christine (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences)
In the last few decades, there has been much progress on low loss waveguides, very efficient photon-number detectors and nonlinear processes. Engineered sum-frequency conversion is now at a stage where it allows operation on arbitrary temporal broadband modes, thus making the spectral degree of freedom accessible for information coding. Hereby the information is often encoded into the temporal modes of a single photon. Here, we analyse the prospect of using multi-photon states or squeezed states in different temporal modes based on integrated optics devices. We describe an analogy between mode-selective sum-frequency conversion and a network of spatial beam splitters. Furthermore, we analyse the limits on the achievable squeezing in waveguides with current technology and the loss limits in the conversion process. This article is part of the themed issue ‘Quantum technology for the 21st century’.